2023
DOI: 10.1039/d2cs00142j
|View full text |Cite
|
Sign up to set email alerts
|

Chemically engineering cells for precision medicine

Abstract: This review summarizes chemical tools for cell engineering, introduces their wide application in diagnosis and therapy, and discusses the challenges and opportunities in precision medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 296 publications
(402 reference statements)
0
19
0
Order By: Relevance
“…As an interdisciplinary field, drug delivery sources information mainly from three areas, the knowledge of pharmacokinetics and the pharmacology of drugs in vivo ( Niu et al, 2021a ; Wang et al, 2022 ; Meng et al, 2022 ; Tang et al, 2022 ; Wang and Feng, 2022 ; Wu et al, 2022 ), new types of pharmaceutical excipients for carrying the drug molecules to the lesion locations ( Murugesan and Raman, 2021 ; Li C. F. et al, 2022 ; Wang L. et al, 2022 ; Zhu et al, 2022 ; Wang et al, 2023 ; Kostka et al, 2023 ), and new pharmaceutical techniques and related strategies, which are often introduced from other disciplines ( Chen et al, 2022 ; Xie et al, 2022 ; Song et al, 2023a ; Wang et al, 2023 ; Chen et al, 2023 ; Huang and Feng, 2023 ). During the past several decades, the effective combination of these three aspects has continuously updated the commercial drug dosage forms for a more efficient, safer, and more convenient drug administration process ( Fatema et al, 2022 ; Hopkins et al, 2022 ; Shen et al, 2022 ; Zhao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an interdisciplinary field, drug delivery sources information mainly from three areas, the knowledge of pharmacokinetics and the pharmacology of drugs in vivo ( Niu et al, 2021a ; Wang et al, 2022 ; Meng et al, 2022 ; Tang et al, 2022 ; Wang and Feng, 2022 ; Wu et al, 2022 ), new types of pharmaceutical excipients for carrying the drug molecules to the lesion locations ( Murugesan and Raman, 2021 ; Li C. F. et al, 2022 ; Wang L. et al, 2022 ; Zhu et al, 2022 ; Wang et al, 2023 ; Kostka et al, 2023 ), and new pharmaceutical techniques and related strategies, which are often introduced from other disciplines ( Chen et al, 2022 ; Xie et al, 2022 ; Song et al, 2023a ; Wang et al, 2023 ; Chen et al, 2023 ; Huang and Feng, 2023 ). During the past several decades, the effective combination of these three aspects has continuously updated the commercial drug dosage forms for a more efficient, safer, and more convenient drug administration process ( Fatema et al, 2022 ; Hopkins et al, 2022 ; Shen et al, 2022 ; Zhao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“… [20–22] These inherent advantages facilitate the effective utilization of these biomaterials for the targeted delivery of therapeutics to diverse cell types such as T cells, macrophages, dendritic cells (DC), and stem cells. Consequently, significant advances have been made in the fields of cancer immunotherapy, bacterial therapies, and anti‐inflammatory treatments [14,23] …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, significant advances have been made in the fields of cancer immunotherapy, bacterial therapies, and anti-inflammatory treatments. [14,23] Here, we provide an overview of recent advances in biomaterials used for in situ cell reprogramming. Specifically, we focus on biomaterials to engineer four specific cell types: T cells, macrophages, DC, and stem cells.…”
mentioning
confidence: 99%
“…The proliferative and migratory ability of cells is crucial for living cell-based drug delivery systems. , Results indicated that n-RX and l-RX had similar proliferative abilities after incubation in culture medium (Figure a), suggesting that the cholesterol removal strategy did not affect the proliferation rate of cells. This treatment also had no effect on the migratory ability of cells, as confirmed by the transwell study (Figure b).…”
mentioning
confidence: 99%
“…However, compared with common delivery vehicles, such as polymeric nanoparticles and extracellular vesicles, living cells are generally more sensitive to the in vivo environment. This is because, in many cases, they are larger, more complex, more fragile, and naturally responsive to various biological signals, which may diminish their targeting function . As intravenous injection is the major route of drug administration whereby delivery vehicles are directly injected into the blood, one important aspect of the in vivo environment is fluid shear stress (FSS), which occurs due to the blood flow. Generally, FSS levels fluctuate between 0.4 and 6 Pa in veins, arteries, lymphatics and capillaries; this is strong enough to effectively stimulate mechanical force-sensing pathways in cells. , It has been reported that blood FSS may increase the level of reactive oxygen species (ROS) in cells, which damages their mitochondria and induces cell death. , Thus, enhancing the adaptability of cells to FSS may improve their survival rate in the blood …”
mentioning
confidence: 99%